Combined Effects of Sawdust and Building Rubbles as Aggregate on the Concrete - Atwan, Dalia Shakir (Al-Nahrain Journal for Engineering Sciences, 2017)
Most of building rubbles or wastes contain some damaged materials such as cement, brick, steel, ceramic, plastic and other substances. Among these materials, ceramic and brick when using both of them as a partial replacement by the weight of conventional coarse aggregate in mixture concrete with presence of variety ratios ( 10% to 30%) for sawdust as replacement of fine aggregate, the resulting concrete properties will affected. So, this paper was based on the study some properties of concrete that produced of 50% replacement for those rubbles plus to presence 10%, 20% and 30% sawdust for both of them. The results revealed that present of sawdust with each of type of those rubbles provides database which are potential to be used in the production of lighter and economical new concrete material. Furthermore, the higher ratios of sawdust (more than 10 %) lead to obvious affected on the strength as well as other properties. While, those negative effects will perceptible improved when added 10% sawdust in ceramic aggregate concrete compared to brick aggregate concrete.